Role of the coagulation system in genitourinary cancers: Review - John, Axel; Gorzelanny, Christian; Bauer, Alexander; Schneider, Stefan W. (Clinical genitourinary cancer, 2018)
Tumor progression is associated with aberrant hemostasis, and patients with malignant diseases have an elevated risk of developing thrombosis. A crosstalk among the vascular endothelium, components of the coagulation cascade, and cancer cells transforms the intravascular milieu to a prothrombotic, proinflammatory, and cell-adhesive state. We review the existing evidence on activation of the coagulation system and its implication in genitourinary malignancies and discuss the potential therapeutic benefit of antithrombotic agents. A literature review was performed searching the Medline database and the Cochrane Library for original articles and reviews. A second search identified studies reporting on oncological benefit of anticoagulants in genitourinary cancer. An elevated expression of procoagulatory tissue factor on tumor cells and tumor-derived microparticles seems to stimulate cancer development and progression. Several components of the hemostatic system, including D-dimers, von Willebrand Factor, thrombin, fibrin-/ogen, soluble P-selectin, and prothrombin fragments 1 + 2 were either overexpressed or overactive in genitourinary cancers. Hypercoagulation was in general associated with a poorer prognosis. Experimental models and small trials in humans showed reduced cancer progression after treatment with anticoagulants. Main limitations of these studies were heterogeneous experimental methodology, small patient numbers, and a lack of prospective validation. In conclusion, experimental and clinical evidence suggests procoagulatory activity of genitourinary neoplasms, particularly in prostate, bladder and kidney cancer. This may promote the risk of vascular thrombosis but also metastatic progression. Clinical studies linked elevated biomarkers of hemostasis with poor prognosis in patients with genitourinary cancers. Thus, anticoagulation may have a therapeutic role beyond prevention of thromboembolism.